Pola Lafal Bunyi Khusus Bahasa Jepang pada Tuturan Pembelajar Bahasa Jepang di Indonesia - Najoan, Franky Reymond (Universitas Muhammadiyah Yogyakarta, 2019)
One of the most difficult parts of Japanese language acquisition is a feature sound called special morae and its relation to accent. Previous researches have tried to overcome such a problem by using several methods, but the results have not been satisfactory yet. This research aims to identify pronunciation patterns used by the learners and find out the solutions to the problem. The researcher collected the data through an audio recording of 13 students who were to pronounce a list of words and sentences. Then, the data were analyzed using a speech analyzer. The results showed that out of 13 students pronouncing 13 stimuli words and 13 sentences that contained those stimuli words, only two students (15.4%) could pronounce those words close to native speaker-like. The variation of speech patterns indicates that the pronunciation pattern of the learners was in the inter-language position when acquiring the Japanese phonemes.